Correlates of well-being among Canadians with mood and/or anxiety disorders - Orpana, H. (Health Promot Chronic Dis Prev Can, 2016)
INTRODUCTION: Our objective was to examine variables associated with well-being as measured by high self-rated mental health (SRMH) and life satisfaction (LS), among Canadian adults (aged 18+) living with a mood and/or an anxiety disorder. METHODS: We used nationally representative data from the 2014 Survey on Living with Chronic Diseases in Canada–Mood and Anxiety Disorders Component (SLCDC-MA) to describe the association between well-being and self-management behaviours (physical activity, sleep and meditation) as well as perceived stress, coping and social support. We used multivariate logistic regression to model the relationship between these factors and measures of well-being. RESULTS: Approximately one in three individuals with mood and/or anxiety disorders reported high SRMH. The logistic regression models demonstrated that several characteristics such as being older, and reporting higher self-rated general health, fewer functional limitations, lower levels of perceived life stress, higher levels of perceived coping and higher levels of perceived social support were associated with higher levels of wellbeing. Self-management behaviours (including starting physical activity, meditation, adopting good sleep habits and attaining a certain number of hours of nightly sleep) were not significantly associated with measures of well-being in our multivariate model. CONCLUSION: Canadian adults with mood and/or anxiety disorders who reported lower levels of perceived stress and higher levels of social support and coping were more likely to report high levels of well-being. This study contributes evidence from a representative population-based sample indicating well-being is achievable, even in the presence of a mood and/or an anxiety disorder.